2011
DOI: 10.1007/s11703-011-1059-5
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of abiotic factors on population fluctuation of insect fauna of Vigna radiata and Tetranychus urticae Koch in Sindh, Pakistan

Abstract: Effect of temperature and relative humidity on population dynamics of insect pests of mung bean was studied during mung bean growing season of 2005. Insect pests included thrips (Thrips tabaci Lind.) and field cricket (Gryllus assimilis) and one arachnid pest mite (Tetranychus urticae Koch). Results revealed that the maximum population of thrips and mites was observed on August 23, 2005 with 1.537±0.031 per leaf and July 6, 2005 with 3.271± 0.09 per leaf, respectively. The population of field cricket differed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
(9 reference statements)
1
3
0
Order By: Relevance
“…2). Consequently, increase in early season temperature may increase mite abundance and have a more negative effect on strawberry plants in respect to foliage damage by mites, which is in line with other studies showing the stimulating effect of increased temperature on mite development (White and Liburd, 2005;Khan, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…2). Consequently, increase in early season temperature may increase mite abundance and have a more negative effect on strawberry plants in respect to foliage damage by mites, which is in line with other studies showing the stimulating effect of increased temperature on mite development (White and Liburd, 2005;Khan, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…According to Ghouri and McFarlane (1958) and Clifford and Woodring (1990), humidity should be below 50% for A. domesticus. A study of wild populations of field crickets in mung bean crops in Pakistan (Khan et al, 2011) also indicated that humidity is of significant importance. That study showed that population size reached its maximum when the crop was in its initial stages, temperature was 33 °C and humidity was 50%, but also that there was a significant negative correlation between the amount of crickets and relative humidity.…”
Section: Discussionmentioning
confidence: 99%
“…The fluctuation of life cycle period in different seasons such as shorter during summer and longer in winter indicated the role of weather parameters in their growth and development which was found similar with other thrips species namely Thrips tabaci, Frankliniella bispinosa etc. on cotton, mung bean and green bean respectively [30][31][32][33]. However, during present investigation apart from seasonality specific effect of temperature and humidity was not measured for each developmental stage.…”
Section: Discussionmentioning
confidence: 64%